A Survey on Robotic Surgery and Autonomous Systems in Modern Medicine including Neonatal Surgical Innovations - Singh, Jaswinder; Dhiman, Gaurav (Journal of Neonatal Surgery, 2025)
Robotic surgery and autonomous systems have emerged as revolutionary technologies in modern medicine, transforming the landscape of surgical procedures, diagnostics, and patient care. This survey paper provides a comprehensive analysis of the advancements in robotic surgery, with a focus on the integration of autonomous systems into the medical field. We explore the evolution of robotic surgical systems, from early robotic assistants to state-of-the-art platforms, highlighting their impact on precision, minimally invasive techniques, and patient outcomes. Additionally, we examine various types of robotic systems, including teleoperated, autonomous, and hybrid models, along with their applications in a wide range of surgeries such as urological, cardiovascular, orthopedic, neonatal, and neurosurgical procedures. Special attention is given to neonatal robotic surgery, where precision and minimally invasive techniques are crucial for delicate procedures on newborns, particularly in cases of congenital anomalies and life-threatening conditions requiring early surgical intervention. The paper discusses the benefits of robotic surgery, including enhanced accuracy, reduced recovery times, and minimized human error, while addressing challenges such as high costs, regulatory hurdles, and the need for extensive clinician training. Furthermore, the role of artificial intelligence (AI) and machine learning (ML) in enhancing robotic surgery's capabilities—particularly in real-time decision-making, navigation, and post-operative care—is examined. The integration of autonomous systems into the operating room, including the development of surgical robots capable of performing tasks independently, is analyzed in depth, exploring their potential to further reduce human intervention and improve surgical precision, especially in neonatal and pediatric surgery, where precision and safety are paramount. Ethical considerations, such as patient safety, privacy concerns, and the potential for job displacement within healthcare systems, are also discussed. This survey aims to provide a comprehensive understanding of the current state of robotic surgery and autonomous systems, while offering insights into their future trajectory in revolutionizing medical practices and improving patient care outcomes, including advancements in neonatal surgical care.